Plasticity of cardiorespiratory neural processing: classification and computational functions - Poon, Chi-Sang; Siniaia, Marina S (Respiration physiology, 2000)
Neural plasticity, or malleability of neuronal structure and function, is an important attribute of the mammalian forebrain and is generally thought to be a kernel of biological intelligence. In this review, we examine some reported manifestations of neural plasticity in the cardiorespiratory system and classify them into four functional categories, integral; differential; memory; and statistical-type plasticity. At the cellular and systems level the myriad forms of cardiorespiratory plasticity display emergent and self-organization properties, use- and disuse-dependent and pairing-specific properties, short-term and long-term potentiation or depression, as well as redundancy in series or parallel structures, convergent pathways or backup and fail–safe surrogate pathways. At the behavioral level, the cardiorespiratory system demonstrates the capability of associative and nonassociative learning, classical and operant conditioning as well as short-term and long-term memory. The remarkable similarity and consistency of the various types of plasticity exhibited at all levels of organization suggest that neural plasticity is integral to cardiorespiratory control and may subserve important physiological functions.